2015
DOI: 10.2217/epi.15.3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms in nanomaterial-induced toxicity

Abstract: With the growing advent of nanotechnology in medicine (therapeutic, diagnostic and imaging applications), cosmetics, electronics, clothing and food industries, exposure to nanomaterials (NMs) is on the rise and therefore exploring their toxic biological effects have gained great significance. In vitro and in vivo studies over the last decade have revealed that NMs have the potential to cause cytotoxicity and genotoxicity although some contradictory reports exist. However, there are only few studies which have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 127 publications
0
57
0
2
Order By: Relevance
“…Although reports on the alterations of the epigenetic integrity by nanoparticles are burgeoning, little efforts have been devoted to probe the impacts of AgNPs on histone modification [10]. Only one study previously reported a particular tropism for CdTe QDs in binding to histone, although no biological impacts were assessed Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although reports on the alterations of the epigenetic integrity by nanoparticles are burgeoning, little efforts have been devoted to probe the impacts of AgNPs on histone modification [10]. Only one study previously reported a particular tropism for CdTe QDs in binding to histone, although no biological impacts were assessed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to a larger number of studies on genotoxic features of nanomaterials, only a few studies have been done to look into their capability to alter epigenetic integrity [10]. Considering the current reports on epigenetic alterations by nanomaterials, most studies were performed with focus on non-coding RNAs, such as miRNAs [10,11]. By contrast, very few studies have been carried out to assess histone modifications [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional activity of a gene can be regulated by epigenetic processes, involving DNA methylation and histone modification and microRNAs(miRs) expression [29]. Lau et al demonstrated that after administration of a DNA methyltransferase inhibitor, the expression profile of AChE changed dramatically during the myogenesis process in C2C12 cells [30].…”
Section: Potential Roles Of Dna Methylation and Histone Modificationmentioning
confidence: 99%
“…In the era of "nano", we should not fear but control the use of nanomaterials. Cytotoxicity genotoxicity as well as possible toxicity due to epigenetic mechanisms should be focused in future studied [5]. …”
Section: Open Access Editorialmentioning
confidence: 99%